2023
DOI: 10.1021/acs.jpcc.3c05351
|View full text |Cite
|
Sign up to set email alerts
|

pH Sensing Based on Ionic Current Rectification Using Triple-Barreled Glass Microelectrodes

Tatsunori Kishimoto,
Kentaro Doi

Abstract: Glass nanopores are known to provide proton selectivity in ionic current conditions in which silanol groups that fill glass surfaces support proton conduction along the surfaces in aqueous solutions. Negatively charged glass surfaces furthermore exclude anions from the glass nanopores. Therefore, glass electrodes are often used for the probes of pH sensors. We focused on the ion selectivity and ionic current rectification of glass nanopores. In this study, we propose triple-barreled glass microelectrodes that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…We have also investigated ICR effects on ion selectivity in micro- and nanofluidic channels, which are applied to EHD flows through ion-exchange membranes [ 31 , 32 ] and proton concentration measurements [ 33 , 34 ]. The results suggested that EOF and EHD flows could be induced with quite low ion concentrations [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…We have also investigated ICR effects on ion selectivity in micro- and nanofluidic channels, which are applied to EHD flows through ion-exchange membranes [ 31 , 32 ] and proton concentration measurements [ 33 , 34 ]. The results suggested that EOF and EHD flows could be induced with quite low ion concentrations [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results suggested that EOF and EHD flows could be induced with quite low ion concentrations [ 13 ]. The ion selectivity is possibly improved as the ion concentration decreases [ 13 , 33 , 34 ] because EDLs in nanochannels tend to overlap between opposite surfaces at quite low concentrations with electrical charge carriers limited to surface charges [ 11 ]. Furthermore, ion concentration gradients in a nanochannel cause diffusion in ionic currents along the channel [ 8 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations